First Report of Temnocephala brevicornis Monticelli 1889 (Temnocephalidae: Platyhelminthes) in Argentina - Brusa, Francisco (2000)
Temnocephala brevicornis Monticelli 1889, ectosymbiont of Hydromedusa tectifera Cope 1869, is reported for the first time for Argentina. Numerous temnocephalans from Arroyo Villoldo in the locality of Magdalena, Buenos Aires, Argentina were stained in toto to be studied. This commensal species in turtles was originally cited in association with Hydromedusa maximiliani (Mikan) and Hydraspis radiolata Mikan in Brazil. Afterwards, it was found on other fresh water turtle species in Brazil and Uruguay.